2019
DOI: 10.3390/f10090712
|View full text |Cite
|
Sign up to set email alerts
|

Differential Trends of Qinghai Spruce Growth with Elevation in Northwestern China during the Recent Warming Hiatus

Abstract: Tree growth strongly responds to climate change, especially in semiarid mountainous areas. In recent decades, China has experienced dramatic climate warming; however, after 2000 the warming trend substantially slowed (indicative of a warming hiatus) in the semiarid areas of China. The responses of tree growth in respect to elevation during this warming hiatus are poorly understood. Here, we present the responses of Qinghai spruce (Picea crassifolia Kom.) growth to warming using a stand-total sampling strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Therefore, to assess the impacts of future climate change on forest growth, it is crucial to study the climatic forcing of tree growth at annual and seasonal time scales. However, a number of studies about growth-climate relationships were mostly based on tree-ring-based investigations [7][8][9][10]. Such studies do not fully explain the effects of climate conditions on tree growth and do Forests 2022, 13, 388 2 of 14 not capture seasonal growth changes and relevant growth-limiting factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to assess the impacts of future climate change on forest growth, it is crucial to study the climatic forcing of tree growth at annual and seasonal time scales. However, a number of studies about growth-climate relationships were mostly based on tree-ring-based investigations [7][8][9][10]. Such studies do not fully explain the effects of climate conditions on tree growth and do Forests 2022, 13, 388 2 of 14 not capture seasonal growth changes and relevant growth-limiting factors.…”
Section: Introductionmentioning
confidence: 99%
“…tree growing in this region is a native evergreen conifer growing at an elevation of 2500-3300 m a.s.l. [7,9]. Earlier studies showed that daily and seasonal variation in stem growth of Qinghai spruce trees at the single scale and among tree classes, and that stem growth initiation was governed by air temperature and/or soil temperature [20,[23][24][25], and that growth cessation was affected by soil moisture under drought conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…The species provides significant ecological functions, including the conservation of water resources and biodiversity, and the maintenance of ecological safety [17]. Recently, studies of P. crassifolia have focused on its growth response and adaption to global warming from a physiological perspective [18,19]. Yet knowledge remains limited regarding the response of P. crassifolia's leaf stoichiometry to environmental changes along elevational gradients.…”
Section: Introductionmentioning
confidence: 99%
“…), located on a northwest-facing slope with a slope gradient of 27 • (Figure 1c). The forest in the plot consisted of Qinghai spruce ranging from 45 to 115 years in age [27]. The canopy density, i.e., the ratio of the total projected area of all trees to the total stand area, was 0.55.…”
Section: Research Plotmentioning
confidence: 99%